CXCR6+ NK Cells in Human Fetal Liver and Spleen Possess Unique Phenotypic and Functional Capabilities - Angelo, Laura S.; Bimler, Lynn H.; Nikzad, Rana; Aviles-Padilla, Kevin; Paust, Silke (Frontiers in Immunology, 2019)
Tissue-resident Natural Killer (NK) cells vary in phenotype according to tissue origin, but are typically CD56bright, CXCR6+, and CD69+. NK cells appear very early in fetal development, but little is known about when markers of tissue residency appear during gestation and whether the expression of these markers, most notably the chemokine receptor CXCR6, are associated with differences in functional capability. Using multi-parametric flow cytometry, we interrogated fetal liver and spleen NK cells for the expression of a multitude of extracellular markers associated with NK cell maturation, differentiation, and migration. We analyzed total NK cells from fetal liver and spleen and compared them to their peripheral blood (PB) and adult liver and spleen counterparts. We found that fetal NK cells resemble each other and their adult counterparts more than PB NK. Maturity markers including CD16, CD57 and KIR are lower in fetal NK cells than PB, and markers associated with an immature phenotype are higher in fetal liver and spleen NK cells (NKG2A, CD94, and CD27). However, T-bet/EOMES transcription factor profiles are similar amongst fetal and adult liver and spleen NK cells (T-bet–/EOMES+) but differ from PB NK cells (T-bet+EOMES–). Further, donor-matched fetal liver and spleen NK cells share similar patterns of expression for most markers as a function of gestational age. We also performed functional studies including degranulation, cytotoxicity, and antibody-dependent cellular cytotoxicity (ADCC) assays. Fetal liver and spleen NK cells displayed limited cytotoxic effector function in chromium release assays but produced copious amounts of TNFα and IFNγ, and degranulated efficiently in response to stimulation with PMA/ionomycin. Further, CXCR6+ NK cells in fetal liver and spleen produce more cytokines and degranulate more robustly than their CXCR6– counterparts, even though CXCR6+ NK cells in fetal liver and spleen possess an immature phenotype. Major differences between CXCR6– and + NK cells subsets appear to occur later in development, as a distinct CXCR6+ NK cell phenotype is much more clearly defined in PB. In conclusion, fetal liver and spleen NK cells share similar phenotypes, resemble their adult counterparts, and already possess a distinct CXCR6+ NK cell population with discrete functional capabilities.